Emotion and Proactivity at Work Prospects and Dialogues - Peng, Kelly Z.; Wu, Chia-Huei (Bristol University Press, 2021)
"EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Individuals' behaviours at work are known to be shaped by cold, or cognitive-motivational, processes as well as hot, or affect-motivational, processes. To date, employee proactivity research has mainly focused on the 'cold' side. But emotion has been proposed to 'energize' employees' proactivity, especially in interdependent and uncertain work environments. In this pioneering work, expert scholars offer new thinking on the process by examining how emotion can drive employees' proactivity in the workplace and how, in turn, that proactivity can shape one's emotional experiences. "